The Stress System of English Loanwords in Qassimi Arabic: An Optimality Theoretic Analysis - Alluhaidan, Nuha Naser (Journal of Humanities & Social Sciences, 2024)
The current paper examines the stress system of English loanwords as used by Qassimi Arabic (QA henceforth) speakers. It specifically conducts an optimality theory (OT) analysis of stress assignment of English borrowed words as uttered by QA speakers. The paper mainly seeks to investigate how stress is assigned in loanwords with different syllable types and syllable numbers, and how optimality accounts for it. The data in the paper are collected from previous studies as well as QA speakers. They are analyzed by the researcher using a number of markedness as well as alignment optimality constraints. It is found that stress assignment in English loanwords is adapted to the stress system of QA. Therefore, the ranking of OT constraints of borrowed English words is the same as that of original Qassimi Arabic words. The researcher concludes that QA stress system is well described and justified using the OT analysis.